Factors Affecting Adoption of Biogas Technology in Dairy Cattle Breeders in Pinang Village, Cendana Sub District, Enrekang District - R. B. Halim; T. Rasyid; M. Aminawar (Jurnal Ilmu dan Teknologi Peternakan, 2016)
So far, many public complaints regarding the negative impact of livestock activities were due to negligence of most livestock farmers in waste management of their business, even in many situation, some of them dispose the waste into the river, causing environmental pollution. Livestock waste such as feces, urine, orts,  water from cleaning the cattle, and the pens produce not just bad smell but also cause an itching when they are taking a bath in the contaminated rivers. These have triggered criticisms from the community. Treating or processing the waste, not only will reduce the impact on the environment, but also will provide benefits because it can be used to produce fuel. One of the available processing technology is biogas technology. Biogas can be used as economical fuel and also can be used to reduce environmental pollution in rural areas. Biogas technology in Desa Pinang District of Cendana Enrekang initially as an effort to use cow feces as alternative energy and reduce environmental pollution. In connection with that, some issues was emerging in relation to the adoption of biogas among the dairy farmers. The purpose of this study was to determine whether extension, experience, education, and motivation may influence the adoption of biogas technology in Pinang Village, Cendana Sub District, Enrekang District. The research was carried from January to February 2016 in Pinang Village, Cendana Sub District, Enrekang District. The type of research was quantitative explanatory. The analytical tool used was multiple regression analysis.The results of study showed that the factors influencing the adoption of biogas technology were extension and motivation, while education and experience had no effects on.